2010
DOI: 10.3151/jact.8.145
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Longitudinal Bar Corrosion on Shear Behavior of RC Beams

Abstract: There have been few reports on the shear behavior of reinforced concrete (RC) beams with corroded longitudinal bars, and the influence of longitudinal bar corrosion has yet to be quantified. Given this background, experimental investigations were conducted to investigate the shear behavior of RC beams with corroded longitudinal bars, in which parameters such as corrosion level and shear-span-to-effective-depth-ratio were taken into consideration. Analytical investigations were also performed to evaluate the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 5 publications
0
16
0
Order By: Relevance
“…Several researchers have studied the strength and shear capacity of RC beams with only the stirrups corroded Juarez, Guevara, Fajardo, and Castro-Borges (2011), Higgins and Farrow (2006), Suffern, El-Sayed, and Soudki (2010) or with only corrosion or complete loss of bond of the longitudinal steel bars or corroded longitudinal steel bars Cairns and Zhao (1993), Jeppsson and Thelandersson (2003) Xue and Seki (2010). Others have published the shear strength of RC beams with corroded longitudinal steel and stirrups Wang, Gao, Li, and Deng (2011), Rodriguez, Ortega, and Casal (1997), Xia, Jin, and Li (2011), which represents the actual corrosion in real structures.…”
Section: Introductionmentioning
confidence: 97%
“…Several researchers have studied the strength and shear capacity of RC beams with only the stirrups corroded Juarez, Guevara, Fajardo, and Castro-Borges (2011), Higgins and Farrow (2006), Suffern, El-Sayed, and Soudki (2010) or with only corrosion or complete loss of bond of the longitudinal steel bars or corroded longitudinal steel bars Cairns and Zhao (1993), Jeppsson and Thelandersson (2003) Xue and Seki (2010). Others have published the shear strength of RC beams with corroded longitudinal steel and stirrups Wang, Gao, Li, and Deng (2011), Rodriguez, Ortega, and Casal (1997), Xia, Jin, and Li (2011), which represents the actual corrosion in real structures.…”
Section: Introductionmentioning
confidence: 97%
“…A number of studies (Azam, Soudki 2013, 2012Xue, Seki 2010;Toongeonthong, Meakawa 2004;Satoh et al 2003;Cairns 1995;Raoof, Lin 1997) have been reported in the literature on effect of corrosion on behaviour of RC beams without stirrups. However, these studies assumed proper anchorage of the reinforcement but there may be conditions in service when anchorage is also impaired due to corrosion.…”
Section: Introductionmentioning
confidence: 99%
“…The shear failure was brittle, which would seriously affect the safety of concrete beams (Rodriguez et al 1997). The loss of cross-sectional area would cause a reduction in shear resistance carried by stirrups (Farrow and Higgins 2006;Matsuo et al 2004;Xue and Seki 2010). However, the effects of corrosion on structural deterioration were only reviewed and not investigated sufficiently, and thus further research about it should continue to be conducted.…”
Section: Introductionmentioning
confidence: 99%